Genetic analysis of multiple primary melanomas arising within the boundaries of congenital nevi depigmentosa. (7th May 2021) - Fuiten, Allison M.; Fankhauser, Reilly G.; Smit, Darren J.; Stark, Mitchell S.; Enright, Trevor F.; Wood, Mary A.; DePatie, Nicholas A.; Pivik, Karla; Sturm, Richard A.; Berry, Elizabeth G.; Kulkarni, Rajan P.
Abstract: Here, we present a rare case of a patient who developed multiple primary melanomas within the boundaries of two nevi depigmentosa. The melanomas were excised, and as a preventive measure, the remainder of the nevi depigmentosa were removed. We performed whole‐exome sequencing on excised tissue from the nevus depigmentosus, adjacent normal skin, and saliva to explain this intriguing phenomenon. We also performed a GeneTrails Comprehensive Solid Tumor Panel analysis on one of the melanoma tissues. Genetic analysis revealed germline MC1R V92M and TYR R402Q polymorphisms and a MET E168D germline mutation that may have increased the risk of melanoma development. This genetic predisposition, combined with a patient‐reported history of substantial sun exposure and sunburns, which were more severe within the boundaries of the nevi depigmentosa due to the lack of photoprotective melanin, produced numerous somatic mutations in the melanocytes of the nevi depigmentosa. Fitting with this paradigm for melanoma development in chronically sun‐damaged skin, the patient's melanomas harbored somatic mutations in CDKN2A (splice site), NF1, and ATRX and had a tumor mutation burden in the 90–95th percentile for melanoma.